A Numerical Study on the Design of a Diffuser Nozzle for Pulsed-Jet Cleaning of Cone Filter Cartridges - Bin Yang; Jianwu Chen; Jianlong Li; Wenjun Xie; Quanquan Wu; Da You; Shan Huang; Shukai Sun; Zhongan Jiang (Atmosphere)
For workplaces where the dust cakes have high viscosity, it is difficult to peel the dust cake from the surface of the dust filter cartridge. The problem of poor dust removal restricts the efficient and stable operation of the dust collector. This study proposes a diffuser nozzle to improve the pulsed-jet cleaning performance of cone filter cartridges. Through numerical modeling, the study investigates the improvement of pulsed-jet velocity and pressure by the diffuser nozzle, explores the influence of the diffuser angle (θ) and diffuser distance (D) on the jet field of the cone filter cartridge core, and compares the pulsed-jet intensity and uniformity of the dust removal filter cartridge. The findings show that the diffuser nozzle with appropriate parameters is conducive to enhancing the divergence and entrainment of the jet airflow, reducing the airflow velocity in the filter cartridge opening area and increasing the static pressure, while also increasing the airflow entrainment. The pulsed-jet intensity and uniformity, especially the pulsed-jet intensity in the upper part of the filter cartridge, vary significantly with θ or D, and the action mechanisms of θ or D are obtained. Under the recommended diffuser nozzle parameters (θ = 70° and D = 40 mm), the pulsed-jet intensity is 1086 Pa, which is 5.4% higher than that under the condition of the common round nozzle; the uniformity coefficient is 0.14, which is 60.0% better than that under the condition of the common round nozzle. For the upper part of the filter cartridge, the pulsed-jet intensity is 1.39 times that with the common nozzle. The result is significant as it offers a guide for improving the pulse-jet cleaning of dust removal filter cartridges.